Silicon wet etching: hillock formation mechanisms and dynamic scaling properties - Mirabella, D. A. (2013)
Surface roughening due to anisotropic wet etching of silicon was studied experimentally and modeled using the Monte Carlo method. Simulations were used to determine the consequences of site-dependent detachment probabilities on surface morphology for a oneand two-dimensional substrate models, focusing on the formation mechanisms of etch hillocks. Dynamic scaling properties of the 1D model were also studied. Resorting to the height?height correlation function and the structure factor, it is shown that the model presents conventional and anomalous scaling (faceted) depending on the stability of the hillocks tops. We also found that there is an intermediate regime that cannot be described by the Family-Vicsek or anomalous scaling ansatz.